1999
DOI: 10.1111/j.1745-459x.1999.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Monadic and Simultaneous Sample Presentation Modes in a Descriptive Analysis of Milk Chocolate

Abstract: Monadic (one sample served at a time, and all attributes rated for that sample) and simultaneous multiple (4 samples served together, and attributes rated one at a time across samples) presentation and evaluation procedures were compared in terms of descriptive profile generated, panel performance (ability to discriminate, reproducibility, concept alignment) and session duration, in a descriptive analysis of 9 milk chocolate samples by a panel of 18 trained judges. The sensory profiles obtained with the two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
0
17
1
1
Order By: Relevance
“…In previous studies, unlike this study, rank-rating showed better performance than monadic rating for intensity evaluations based on different stimulus error rates and discrimination abilities (10,13,16,17). The occurrence of errors during sensory evaluation is largely due to sensory adaptation and forgetting the taste intensity of previously tasted samples (13).…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…In previous studies, unlike this study, rank-rating showed better performance than monadic rating for intensity evaluations based on different stimulus error rates and discrimination abilities (10,13,16,17). The occurrence of errors during sensory evaluation is largely due to sensory adaptation and forgetting the taste intensity of previously tasted samples (13).…”
Section: Resultscontrasting
confidence: 66%
“…Panelists compare the intensities of multiple samples all together and reduce the forgetting effect in ranking method whereas a score is given for the intensity of sample in rating method. Scoring of rating methods can be done based on comparison of multiple samples together (13) or based on evaluation of samples monadically with reliance on a self-structured absolute scale (17). Giving a score for perceived intensity of a sample implies that panelist needs to pick a value from 1-15 numerical scale which in turn forces the panelist to do an additional perceptual process.…”
Section: Resultsmentioning
confidence: 99%
“…If the intensity of an attribute for the first food were to be forgotten while the third food was being assessed, it would not matter. Mazzucchelli and Guinard (1999) compared monadic and attribute-by-attribute protocols, in a related samples design, for descriptive analysis of nine formulations of milk chocolate. During training, 18 judges developed 20 sensory attributes for the chocolates.…”
Section: Introductionmentioning
confidence: 99%
“…This error may be enhanced by the SDM, where assessors were presented with one sample at a time, and not being able to contrast it with other samples, tended to measure all samples in a reduced range. MAZZUCCHELLI and GUINARD (1999) found that assessors discriminated better and were more reproducible when evaluating samples simultaneously in comparison to monadic presentation. PARK and coworkers (2007) found that in a rank-rating procedure, similar to simultaneous sample presentation, there were fewer errors than with a monadic presentation of samples.…”
Section: Spaghettimentioning
confidence: 99%